Sexual Assault Survivors and Information: Needs and Recommendations - Brown, Stephanie (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2022)
This paper examines the information needs of sexual assault survivors, with a focus on the kinds of information these individuals may be seeking and how libraries can best assist survivors with their information needs. The paper begins with an overview of sexual assault as a pervasive problem in society in order to form a basis of understanding of what a sexual assault survivor may be going through and the kinds of barriers that may affect their information seeking. The information needs of sexual assault survivors are complex because of their experiences of violence and trauma, and these factors often result in mental and physical health challenges, and potentially distressing information seeking experiences. In order to best serve sexual assault survivors in libraries, I recommend a trauma-informed approach to librarianship, which underscores the importance of safety, empathy, and empowerment for the survivor. A trauma-informed approach to librarianship can assist sexual assault survivors in remedying potential distress through forming trust, validating their experiences and identity, valuing their voice, and ultimately, supporting their healing.